Myocardial Ischemia: Etiology, Pathophysiology, And Modern Management Approaches - Turdiyev, Mavlonbek; Xojimatov, Dilshod; Yusufjonov, Jasurbek; Qodirov, Iqboljon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
Myocardial infarction (MI) remains one of the leading causes of morbidity and mortality Myocardial ischemia is a common cardiovascular disorder resulting from an imbalance between myocardial oxygen supply and demand, primarily caused by atherosclerotic coronary artery disease. It is a leading cause of morbidity and mortality worldwide, contributing significantly to the global burden of cardiovascular disease. The pathophysiology of myocardial ischemia involves endothelial dysfunction, plaque formation, coronary artery stenosis, and subsequent reduced blood flow to the myocardium. Risk factors include hypertension, diabetes mellitus, dyslipidemia, smoking, sedentary lifestyle, and genetic predisposition. Clinically, patients present with angina pectoris, dyspnea, palpitations, fatigue, and, in severe cases, acute coronary syndrome or myocardial infarction. Diagnosis relies on a combination of clinical evaluation, electrocardiography (ECG), echocardiography, laboratory biomarkers (troponins, CK-MB), and coronary angiography. Management strategies include pharmacological treatment, such as antiplatelet agents, beta-blockers, nitrates, statins, and angiotensin-converting enzyme inhibitors, aimed at relieving symptoms and preventing disease progression. Invasive interventions, including percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG), are indicated in patients with severe stenosis or refractory symptoms. Lifestyle modifications, risk factor management, and cardiac rehabilitation are essential components of comprehensive care. Recent studies highlight the importance of integrating clinical, biochemical, and imaging findings to personalize therapy and improve patient outcomes. Early diagnosis, timely intervention, and multidisciplinary management significantly reduce complications, including heart failure, arrhythmias, and sudden cardiac death. This review summarizes current knowledge on the etiology, pathophysiology, clinical manifestations, and contemporary therapeutic approaches for myocardial ischemia, emphasizing evidence-based management and the importance of preventive strategies to reduce cardiovascular risk and enhance quality of life.